Source Model and Simulated Strong Ground Motion of the 2021 Yangbi, China Shallow Earthquake Constrained by InSAR Observations - Yongzhe Wang; Kun Chen; Ying Shi; Xu Zhang; Shi Chen; Ping’en Li; Donghua Lu (Remote Sensing, 2021)
On 21 May 2021, an Mw 6.1 earthquake, causing considerable seismic damage, occurred in Yangbi County, Yunnan Province of China. To better understand the surface deformation pattern, source characteristics, seismic effect on nearby faults, and strong ground motion, we processed the ascending and descending SAR images using the interferometric synthetic aperture radar (InSAR) technique to capture the radar line-of-sight (LOS) directional and 2.5-dimensional deformation. The source model was inverted from the LOS deformation observations. We further analyzed the Coulomb failure stress (CFS) transfer and peak ground acceleration (PGA) simulation based on the preferred source model. The results suggest that the 2021 Yangbi earthquake was dextral faulting with the maximum slip of 0.9 m on an unknown blind shallow fault, and the total geodetic moment was 1.4 × 1018 Nm (Mw 6.06). Comprehensive analysis of the CFS transfer and geological tectonics suggests that the Dian–Xibei pull-apart basin is still suffering high seismic hazards. The PGA result demonstrates that the seismic intensity of this event reached up to VIII. The entire process from InSAR deformation to source modeling and strong ground motion simulation suggests that the InSAR technique will play an important role in the assessment of earthquake disasters in the case of the shortening of the SAR imaging interval.